OSTEOPOROSIS AND MODERN METHODS OF ITS TREATMENT (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Osteoporosis is a bone disease characterized by increased fragility and brittleness. The reason for this is a lack of calcium in the body, a metabolic disorder due to a lack of calcium element in the bone system in general. People with osteoporosis are life-threatening because simple injuries or collisions can lead to broken bones, such as knocking hands and feet against equipment such as doors, tables, and stools. Situations that are normal for a healthy person can be dangerous for people with osteoporosis.